1983
DOI: 10.1177/002246698301700212
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Attainment in Preschool Children: Analysis of Concordance Between Parents and Professionals

Abstract: P.L. 94-142 mandates parent participation in the evaluation of their children's difficulties. The authors discuss parents' reports of their children's current development, in contrast to previous studies that have relied on parents' memory of their children's developmental mile-stones. A 34-item checklist was developed to document parents' perceptions of their children's strengths and weaknesses in developmental and skill-related areas. A total of 287 preschool children with a mean age of 5 years-1 month were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…While a history of pregnancy and birth complications has been found in identified learning-disabled students (Colletti, 1979) only minor correlations emerge between perinatal status and subsequent intelligence within a non-identified, healthy sample (Bee et al, 1982). Secondly, retrospective parental reporting can result in inaccuracies not observed in concurrent reporting and thus could reduce predictive validity (Meltzer et al, 1983). Meltzer èt al.…”
Section: Parental Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…While a history of pregnancy and birth complications has been found in identified learning-disabled students (Colletti, 1979) only minor correlations emerge between perinatal status and subsequent intelligence within a non-identified, healthy sample (Bee et al, 1982). Secondly, retrospective parental reporting can result in inaccuracies not observed in concurrent reporting and thus could reduce predictive validity (Meltzer et al, 1983). Meltzer èt al.…”
Section: Parental Reportmentioning
confidence: 99%
“…Mothers and fathers have a wealth of information regarding their children's behavior outside of the school setting which can be very helpful in diagnosis of learning problems and subsequent educational planning. A study conducted byMeltzer, Levine, Hanson, Wasserman, Schneider, and Sullivan (1983) demonstrated the parents utility in the evaluation process. The parents responses on a 34-item checklist were generally consistent with the results of a professionally adminstered battery of tests.…”
mentioning
confidence: 99%